Pengaruh Kompensasi dan Lingkungan Kerja terhadap Kinerja Pegawai pada BPPSDMP Kementerian Pertanian Jakarta - Zahratunnisa, Ida; Kurniasari, Rani (www.bsi.ac.id, 2023)
This study was conducted with the aim of knowing and analyzing the effect of compensation and work environment partially and simultaneously on employee performance at BPPSDMP Ministry of Agriculture Jakarta. The data collection method in this study was carried out by distributing questionnaires to 48 respondents, then the sampling technique used in this study used saturated samples. The scale used in this study is the Likert scale. The data source is obtained using primary data and secondary data. Primary data was obtained through the distribution of questionnaires to BPPSDMP employees of the Ministry of Agriculture Jakarta. While secondary data is obtained through books and journals related to research. This research was assisted by SPSS software for windows. The results of the study partially show that Compensation has a positive and significant effect on Employee Performance and the Work Environment has a negative and significant influence on Employee Performance at the BPPSDMP of the Ministry of Agriculture Jakarta. And the results of the study simultaneously show that Compensation and Work Environment have a positive and significant effect on performance at the BPPSDMP of the Ministry of Agriculture Jakarta.Keywords : Compensation, Work Environment, Employee Performance